The voices behind Maria Ligaya Nava, Elena T. Sipin and Carmina Liwanagan - de la Cruz, Anthony S.
This study is a content analysis of the front-page columns of the Philippine Collegian namely Disturbing the Peace, Little Earthquakes and Between the Lines, which were published in separate academic years and written under a pseudonym. These columns reflect the newspaper's depiction of social reality as they tackle issues deemed relevant at the time of publication-the ideological debates on activism during Ibarra Gutierrez's term (Disturbing the Peace), the two consecutive controversies on the Philippine Collegian editorial examination during Voltaire Veneracio's term (Little Earthquakes), and fraternity-related violence during Jeanie Bacong's term (Between the Lines), among others. The contents of the columns cover a diverse lot of subjects that are national, local or community-based, and personal. In the 91 editions examines in this study, columnists Maria Ligaya Nava, Elena T. Sipin and Carmina Liuanagan seem to always adhere to an anti-establishment view-the establishment in this study being the UP administration, its projects, programs and policies, and the government, its projects, programs and policies. More often than not, the columns are strongly worded and firm on their arguments, and in some cases, they are even meant to attack certain personalities and institutions. As such, they serve to affirm the Philippine Collegian's anti-establishment character.